“Conveying Away the Trash”: Sweetening Slavery in Matthew Lewis’s Journal of a West India Proprietor, Kept during a Residence in the Island of Jamaica - Plasa, Carl (Romanticism and Victorianism on the Net, 2008)
AbstractThis article examines the role of sugar in Matthew Lewis’s Journal of a West India Proprietor (1834), arguing that, despite its relatively marginal position as an overt content, the commodity provides a felicitous means of understanding the formal dimensions of Lewis’s text, and its negotiation of racial violence, in particular. Throughout the Journal, Lewis figures the Caribbean sugar estate as a kind of utopia, divested of all that made slavery so anathema to its opponents and, in so doing, discursively echoes the processes of refinement entailed in the production of the very substance on which his wealth and status are predicated. Yet even as Lewis’s colonial record aspires towards a condition of discursive and ideological purity, it can never quite reach its goal: the material realities of racial conflict stubbornly obtrude themselves in stray moments, lingering on in fragmentary and vestigial forms, which vitiate the saccharine visions Lewis seeks to promote.